2019
DOI: 10.1007/s42452-019-1182-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of graphene based nano fluids with minimum quantity lubrication in turning of AISI D3 steel

Abstract: Minimum quantity lubrication is an extensively accepted lubrication system owing to its improved heat removal in the machining areas. The purpose of the current study is to examine the effectiveness of graphene based nanofluids in turning on D3 tool steel with minimum quantity lubrication. Experiments were executed with Taguchi's L27 orthogonal matrix array. The effectiveness were examined with the machining parameters under environment (dry condition, flood lubrication and minimum quantity lubrication), cutti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Alumina and hybrid alumina-graphene nanofluid volume concentrations (0.25%, 0.75% and 1.25%) Tool flank wear and nodal temperature reduction of 12.29% and 5.79% is observed in hybrid nano-fluid as compared to Alumina nano-fluid Babu et al (2019) [17] 2 g of graphene nanoparticle +SDBS mixed with ethylene glycol of 250 mL as base fluid under ultrasonication at 35 W, 50 Hz for 1 hour at room temperature ANOVA table for Surface roughness shows percentage contribution of Cooling Environment of 97.34% against machining conditions (cutting speed, feed and depth of cut) Sivaraman & Prakash (2019) [7] n-MoS2 of 0.5 % wt. (60 -80 nm.)…”
Section: Sharma Et Al (2018) [16]mentioning
confidence: 97%
“…Alumina and hybrid alumina-graphene nanofluid volume concentrations (0.25%, 0.75% and 1.25%) Tool flank wear and nodal temperature reduction of 12.29% and 5.79% is observed in hybrid nano-fluid as compared to Alumina nano-fluid Babu et al (2019) [17] 2 g of graphene nanoparticle +SDBS mixed with ethylene glycol of 250 mL as base fluid under ultrasonication at 35 W, 50 Hz for 1 hour at room temperature ANOVA table for Surface roughness shows percentage contribution of Cooling Environment of 97.34% against machining conditions (cutting speed, feed and depth of cut) Sivaraman & Prakash (2019) [7] n-MoS2 of 0.5 % wt. (60 -80 nm.)…”
Section: Sharma Et Al (2018) [16]mentioning
confidence: 97%
“…In the current study, each combination of input parameters was analyzed thrice, and the average value of the associated response data was recorded. For each trial, a new insert was used to eliminate the effect of tool wear [27], [28]. Table 2 demonstrates the experimental design and responses using the L27 orthogonal array.…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…Nano-additives, such as nanoparticles of metals, metal oxides, or carbon-based materials, can impart enhanced tribological properties, better heat transfer capabilities, improved tool life, superior surface finish, and improved stability to cutting fluids [38]. The effect of graphene nanoplatelets on the performance of cutting fluids found that the addition of graphene resulted in reduced cutting forces, lower tool wear, and improved surface finish [39]. In another study, Kumar et al [40] investigated the influence of zinc oxide nanoparticles on the lubrication and cooling properties of cutting fluids and reported that the addition of nanoparticles enhanced the heat dissipation capacity and reduced the coefficient of friction.…”
Section: Nano-additives In Cutting Fluidsmentioning
confidence: 99%